Experimental study on the hydrodynamic characteristics of a combined structure of offshore wind turbine jacket and net cage - Kai WANG; Ruolang HAN; Tiaojian XU; Biao QIU; Fangwei RUAN; Junquan LIU (Zhongguo Jianchuan Yanjiu, 2024)
ObjectiveThis paper proposes a novel structure that combines an offshore wind turbine jacket and aquaculture net cage, and its hydrodynamic characteristics are investigated. Methods Experimental tests are carried out to analyze the horizontal loads on the pile foundations of the combined structure, and the tension in the connection between the jacket and net cage, while considering the effects of water depth, wave height, wave period, wave direction, current velocity and direction, and other parameters. ResultsFor 0-degree regular wave conditions, the maximum horizontal load on the pile foundations is 30.2 N. For 45-degree regular wave conditions, the maximum horizontal load on the pile foundations is 27.5 N. Thus, the maximum horizontal load on the pile foundations under 0-degree regular wave conditions is 9.5% greater than that under 45-degree regular wave conditions. ConclusionsUnder regular wave conditions, the net cage has little influence on the horizontal load on the pile foundations when the wave period is small, while under pure current conditions, the net cage will cause a significant increase in the horizontal load on the pile foundations of the combined structure.